FINANCIAL FEASIBILITY ANALYSIS OF TRANSJATIM CORRIDOR I LUXURY SIDOARJO-SURABAYA-GRESIK ROUTE - Novalia, Kiki Devita; Muhammadun, Haris; Marleno, Risma (Transpublika Publisher, 2024)
Transjatim Corridor I, which runs the Sidoarjo-Surabaya-Gresik route, serves as a crucial road-based mass transportation system in East Java Province, particularly within the Gerbangkertasusila Agglomeration Area. In 2023, the average load factor for Transjatim Corridor I was 120%, with an average of 5-6 thousand passengers per day. This high demand necessitated the addition of a fleet with luxury services. This study aims to analyze the financial feasibility of investing in Transjatim Luxury Corridor I buses. The investment feasibility is assessed by comparing income and expenditure variables. The analysis employs the NPV, Benefit-Cost Ratio (BCR), IRR, and Payback Period (PP) methods. The initial investment expenditure is Rp. 8,207,989,625. Assuming a load factor of 70%, the revenue for different fare alternatives is as follows: Alternative 1 (Rp. 17,500 fare) generates Rp. 5,723,200,000; Alternative 2 (Rp. 16,000 fare) generates Rp. 5,232,640,000; and Alternative 3 (Rp. 15,000 fare) generates Rp. 4,905,600,000. Based on a 6% discount rate, the NPV for all alternatives is greater than 0: Alternative 1 yields Rp. 5,204,972,631; Alternative 2 yields Rp. 2,466,479,592; and Alternative 3 yields Rp. 640,817,566. The IRR values exceed the discount rate, with Alternative 1 at 19.42%, Alternative 2 at 12.54%, and Alternative 3 at 7.74%. The BCR values are all greater than 1: Alternative 1 is 1.30, Alternative 2 is 1.19, and Alternative 3 is 1.11. The PP values are 4 years for Alternative 1, 5 years for Alternative 2, and 6 years for Alternative 3. Thus, all three alternatives are deemed financially feasible.